HOW DOES LOCAL CONTENT TEXT BASED SHARING READING LITERACY MODEL AFFECT THE INDONESIAN LANGUAGE COURSE IN INDONESIAN SENIOR HIGH SCHOOL? (BAGAIMANA MODEL SHARING READING LITERACY BERBASIS KONTEN LOKAL BERPENGARUH PADA PELAJARAN BAHASA INDONESIA DI SEKOLAH MENENGAH ATAS?) - Silvia Marni; Indriani Nisja; Rina Sartika; Islahuddin Islahuddin; Yul Ardi (Jurnal Gramatika, 2022)
This study aims to determine the effect of reading material of Indonesian course by student and teacher in Senior High School. The type of reading is in the form of folklore in the West Sumatra area. This research used quantitativeapproach towards descriptive method. It is to describe the learning effect for students and teachers, where it is related to master a reading with critical reading learning using the Sharing Reading Literacy model. The research subjects were students of class X SMAN 15 Padang studying critical reading material and consisting of 10 classes. The instruments used were questionnaire sheets and interview guidelines. Data were analyzed by using descriptive statistics. Based on the results of data analysis, it shows that 74% of students need critical reading learning resources, 73% of student need critical reading learning media, and 58% of student need critical reading learning methods called Sharing Reading Literacy as required by the learning indicators. It shows that the local content text based sharing model affect the Indonesian Language course in Indonesian Senior High School.